Adaptation Atlas Notebook: Discover solutions / Découvrir des solutions - Steward, Peter; Youngberg, Brayden; Joshi, Namita; Muller, Lolita; Rosenstock, Todd (2025)
This notebook helps users explore evidence-based adaptation solutions for African agriculture by summarizing how different practices affect crop yields. It compiles mean yield differences from hundreds of studies and visualizes how specific interventions, such as soil management, water conservation, or improved varieties, perform across major crops. Users can filter by crop type and examine comparative impacts to quickly identify which practices deliver the strongest productivity benefits. By translating a large evidence base into an accessible, interactive format, the notebook supports practitioners and policymakers in selecting effective, context-appropriate adaptation options.